Overhanging approximal restoration: Clinical and radiography features at Tarogong Public Health Service Indonesia - Muryani, Anna; A., Amaliya; Garna, Devy Firena; Oscandar, Fahmi; Sukartini, Endang (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2016)
Introduction: Overhanging approximal restoration may causes gingival inflammation, periodontal tissue destruction, decreases alveolar bone height, and caries reccurence. Overhanging restoration can be detected clinically and by radiography image. Overhang restorations can occur due to the poor filling procedures, one of which is the limitation of supporting tools. Restoration of teeth done in Puskesmas often found unavailability constraints supporting tools so that in cases of approximal caries often experience overhang. The aim of this study was to evaluate the incidence of overhanging proximal restoration at Tarogong Public Health Centre in Garut Regency West Java Indonesia. Methods: This study was a descriptive cross sectional for the incidence on patient with overhanging approximal restoration who visited at Dental Unit Tarogong Public Health Center in Garut Regency. Intraoral clinical examination was conducted to examine visually and by tactile for the overhang restoration. Periapical radiography examination was taken and became supporting examination. Results: Collected data were 43 cases of overhanging approximal restoration from total 57 patients. The incidence of overhanging approximal restoration were 75,4. Conclusion: The conclusion of this study by radiography was the incidence of overhanging restoration was 75.4 which showed that overhanging restoration approksimal more than good restoration aproksimal at Tarogong Public Health Centre in Garut Regency West Java Indonesia.